SUPERFAST SCANNING BEAM AND SYNTHESIS OF SHORT SIGNAL IN RADIATION FIELD OF MIMO RADAR TRANSMIT ARRAY - B. M. Vovshin; K. V. Kulikov (Российский технологический журнал)
The effects of "superfast scanning beam" and synthesis of "short" (broadband) signal in the radiation field of the antenna array, excited by mutually orthogonal coherent narrowband signals are under consideration. Researches and modeling are carried out for simple and complex probe signals of MIMO radar. Their orthogonality is provided in the frequency domain due to the separation of the central frequency of their spectra. It is shown that this approach based on MIMO radar technology, with a certain choice of signals parameters and array, allows to overcome the limitations on the width of the signal bandwidth for phased an-tenna array of traditional construction.